An In-Depth Study of the Boron and Phosphorous Doping of GeSn. (24th August 2021) - Frauenrath, M.; Kiyek, V.; von den Driesch, N.; Veillerot, M.; Nolot, E.; Buca, D.; Hartmann, J.-M.
Abstract : We have investigated the in situ doping of GeSn with Ge2 H6, SnCl4, B2 H6 (p-type) or PH3 (n-type) at 349 °C, 100 Torr on Ge Strain-relaxed Buffers, themselves on Si(001) substrates. Our aim was to replace the boron and phosphorous doped Ge layers used in previous pin structures with GeSn:B and GeSn:P. The Sn content from Wavelength Dispersive X-ray Fluorescence (WDXRF) was constant around 6.5% for low F(B2 H6 )/F(Ge2 H6 ) and F(PH3 )/2*F(Ge2 H6 ) Mass-Flow Ratios (MFRs). It fell down to 4.9% (GeSn:B) and 6.0% (GeSn:P) for higher MFRs due to the dopant precursors that catalyzed the Ge Growth Rate component. The B atomic concentrations (from Secondary Ion Mass Spectrometry (SIMS)) increased almost linearly with the MFR, reaching values of at most 6.3 × 10 19 cm −3 . B atoms were almost fully electrically active based on Electrochemical Capacitance Voltage (ECV) measurements. WDXRF and SIMS also gave us access to the atomic P concentrations, with values as high as 3.9 × 10 20 cm −3 . Maybe because of the formation of Snm Pn V nanoclusters, the P electrical activation decreased for the highest flows. Only the GeSn:B layers grown at the three highest MFRs exhibited some B and/or Sn surface segregation. Otherwise, a smooth surface with a cross hatch along ⟨110⟩ was present.